2017
DOI: 10.1016/j.bbr.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Prodynorphin and kappa opioid receptor mRNA expression in the brain relates to social status and behavior in male European starlings

Abstract: Numerous animal species display behavioral changes in response to changes in social status or territory possession. For example, in male European starlings only males that acquire nesting sites display high rates of sexual and agonistic behavior. Past studies show that mu and delta opioid receptors regulate behaviors associated with social ascension or defeat. Opioids also act at kappa receptors, with dynorphin binding with the highest affinity; however, the role of these opioids in social behavior has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…With lower social status viewed as a stressor, our findings of increased KOR levels largely fit with the extant animal literature on social processes, and more exactly, with the lone study on social status and KOR (in male European starlets) [23]. Pair bonding, an important social behavior, has been more studied and found to be influenced by KOR in monogamous animals such as titi monkeys and prairie voles [40][41][42].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With lower social status viewed as a stressor, our findings of increased KOR levels largely fit with the extant animal literature on social processes, and more exactly, with the lone study on social status and KOR (in male European starlets) [23]. Pair bonding, an important social behavior, has been more studied and found to be influenced by KOR in monogamous animals such as titi monkeys and prairie voles [40][41][42].…”
Section: Discussionsupporting
confidence: 85%
“…Mice given a KOR antagonist, or lacking a gene for dynorphin (i.e., Pdyn), did not show a typical defeated posture after exposure to repeated social defeats compared with placebo animals [21]. In the nucleus accumbens, an area integral to rewards, KOR-mediated social aversion in prairie voles [22], social status in starlings [23], and in rats there was an upregulation with social isolation [12]. Susceptible and resilient animals have also shown different expression levels of dynorphin mRNA in response to social stressors [24,25], although differences have also been reported in this region and others [26].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies show correlations between a variety of neuronal markers in VTA and bond‐related behaviors observed in males, including the production of courtship and nesting behaviors . Based on these studies, we expected to find that the distinct patterns of gene expression identified between males in the low and high dopamine groups would be associated with differences in the numbers of bond‐related behaviors produced by the males.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the modification of dopamine release from VTA projection neurons via GABA or glutamate receptor antagonist administration directly into VTA induces pair bonding in male prairie voles . The complex interplay among neuromodulators is highlighted further by studies in songbirds, which show that multiple neuronal markers in VTA (eg, cells labeled for immediate early genes, dopamine‐beta‐hydroxylase, vasopressin V1a receptors, tyrosine hydroxylase, neurotensin, opioid neuropeptides and other measures of catecholamine activity) correlate with pairing‐related behaviors (eg, pairing status, courtship behaviors, clumping, allopreening and nesting). It is also noteworthy that markers in VTA can be associated closely with the behavior that an individual receives from a partner …”
Section: Introductionmentioning
confidence: 99%
“…The brain areas originally implicated are the medial amygdala, medial bed nucleus of the stria terminalis, preoptic area, lateral septum, ventromedial and anterior hypothalamus, and the midbrain periaqueductal grey area and tegmentum . These areas are all mutually connected and use numerous hormones (including in particular prolactin and steroids) and peptides (including gonadotrophin‐releasing hormone, gonadotrophin‐inhibitory hormone, neurotensin, opioids and vasoactive intestinal polypeptide), all of which appear to be relevant to individual, species and seasonal differences in social structure …”
Section: Birdsmentioning
confidence: 99%